Effect of Patient Characteristics on Vessel Enhancement in Pediatric Chest Computed Tomography Angiography. Issue 2 (May 2019) - Masuda, Takanori; Nakaura, Takeshi; Funama, Yoshinori; Sato, Tomoyasu; Nitta, Tetsuya; Higaki, Toru; Baba, Yasutaka; Matsumoto, Yoriaki; Imada, Naoyuki; Awai, Kazuo
Introduction: To evaluate the effect of sex, age, height, cardiac output (CO), total body weight (TBW), body surface area (BSA), and lean body weight (LBW) on vessel enhancement of the ascending aorta in pediatric chest computed tomography angiography (c-CTA). Materials and Methods: This retrospective study received institutional review board approval; parental prior informed consent for inclusion was obtained for all patients. All 50 patients were examined using our routine protocol; iodine (600 mg/kg) was the contrast medium (CM). Unenhanced and contrast-enhanced scans were obtained. We calculated the CM volume per vessel enhancement and performed univariate and multivariate linear regression analysis of the relationship between CM volume per vessel enhancement and each of the body parameters. Results: All patient characteristics were significantly related to CM volume per vessel enhancement ( P < .05). Multivariate linear regression analysis revealed a significant correlation between CM volume per vessel enhancement and TBW, BSA, and LBW, but not the patient sex, age, CO, and height. The LBW model for CM volume per vessel enhancement yielded the highest determination coefficient (R 2 = .913) and the lowest Akaike Information Criterion (400.324). Conclusions: Our findings support the delivery of an iodine dose adjusted to the LBW at c-CTA.